Coping Strategies of the Russian Population in Response to Social Risks - Makarova, Mariya N. (Economy of Regions, 2025)
The diversity and intensity of social risks faced by contemporary Russian society contribute to elevated stress levels and a widespread need for adaptation to rapidly changing conditions. Against this backdrop, this study explores coping strategies as behavioural patterns that emerge in response to social risks. While individual and group coping behaviours have been widely examined, population-level coping strategies remain underexplored—particularly in terms of generalization at the macro level (national or regional) and in accounting for both objective factors and subjective perceptions of risk. The study is grounded in the hypothesis that coping strategies are shaped not only by the population’s socio-economic characteristics but also by their subjective perception of life circumstances. In turn, these strategies influence how people perceive, structure, and respond to social risks. The study aims to examine the characteristics of different coping strategies in relation to subjective assessments of social risks that create a stressful environment. Coping strategies were identified through a pilot sociological survey conducted among the working-age population of Sverdlovsk Oblast between April and November 2024. The sample was representative by gender and age and constructed with a 95 % confidence interval. The survey revealed three main coping strategies used in response to social risks: “solve the problem,” “ask for help,” and “wait it out.” The study identifies the socio-demographic characteristics associated with each strategy, highlights the most pressing social risks, and illustrates behavioural responses using the example of health deterioration risk. The novelty of this research lies in addressing both objective and subjective factors that shape coping behaviour. The findings underscore the importance of tailoring social policy measures to specific population groups based on their dominant coping strategy. Future research may expand on these findings by examining additional socio-demographic determinants, such as education level or place of residence, and by refining the classification of each coping strategy.